The enemies of Jupiter - Lawrence, Caroline (London : Orion, 2009)
Jonathan and his friends are called to Rome by the emperor in the winter of 80 A.D. to find the new Prometheus believed to have brought an epidemic to the city, but Jonathan, obsessed with reuniting his parents, makes some unwise--and life-threatening--choices.
First published: London : Orion Children's Books, 2003.
Horn Book.
School Library Journal.
Horn Book, April 2006.
School Library Journal, June 2005.
4.8
Keywords: Berenice, -- b. ca. 28 -- Juvenile fiction; Titus, -- Emperor of Rome, -- 40-81 -- Juvenile fiction; Berenice, -- b. ca. 28 -- Fiction; Titus, -- Emperor of Rome, -- 40-81 -- Fiction; Berenice, -- b. ca. 28 -- Fiction; Titus, -- Emperor of Rome, -- 40-81 -- Fiction; Dysfunctional families -- Juvenile fiction; Epidemics -- Rome -- History -- Juvenile fiction; Epidemics -- Fiction; Family problems -- Fiction; Historical fiction; Mystery and detective stories; Epidemics -- Fiction; Family problems -- Fiction; Historical fiction; Mystery fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Juvenile fiction; Rome -- History -- Empire, 30 B.C.-476 A.D. -- Fiction; Rome -- History -- Fiction; Historical fiction; Mystery fiction